O se-movimentar na ambiência educativa da educação física: contribuições para a formação humana de estudantes dos anos finais - Saitsu, Andréa Cristina (2021)
The research, with a qualitative profile and a theoretical-bibliographic nature, develops reflection educational philosophy on the formative contribution of the Theory of Self-Movement (TSM). Coming from the German expression “Sich-Bewegen”, the Se-Movimentar was spread by authors such as Elenor Kunz and Mauro Betti who sought elements in the propositions called pedagogies criticisms of Physical Education in Brazil, bringing an important theoretical contribution to the Proposal Physical Education Curriculum in the State Teaching Network of the State of São Paulo, in the last decades. Some of these propositions emphasize the need to form critical citizens and autonomous with possibilities of transforming the reality in which they live through a reflective education providing the understanding of the Movement Culture phenomenon as manifestation of human identity that develops as one observes one's own expression of Self-Movement, making the subject dimension conscious, overcoming the reductionist perspective of mere reproduction of mechanical body patterns. This conception seeks to go beyond biological and dichotomous analyzes and explanations, very present in the history of of Physical Education, aiming at human emancipation, whether through reflective criticism based on the frankfurtian matrix, which supports the idea of the possibility of re-elaboration of the knowledge through self-reflection, discarding the deformities that the historical process can have offered, whether in Merleau-Ponty's phenomenology, when analyzing its foundations, observing things in the world and considering that they are always closely linked to the subject who experiences the experience and appropriates it, by embodying symbols and meanings that will also be your identity. Based on the conception of education as mediation fundamental of human formation, supported by Severino and aimed at the pedagogical cultivation of the movement as proposed by TSM, the research aimed to explain the relevance formation of Se-Movimentar, presenting the theoretical debate that, with a view to cultural resizing of the field, presented the conceptual elements of its constitution theory, evidencing the relevance of the support it provides to the Curricular Proposal of the Network State of São Paulo, thus effecting the production of subsidy for the teachers with a view to redirecting the pedagogical practice of Physical Education in school context